Fan Letters to the Cultural Industries: Border Literature about Mass Media - Claire Fox (Studies in 20th & 21st Century Literature, 2001)
The concentration of the Mexican and U.S. cultural industries in cities outside of the border region and the intermittent outsourcing of Hollywood movies to production facilities in Baja, California, have had a marked impact on the literary practice of "fronterizo" 'border' intellectuals. This essay discusses the theme of the cinema in three narratives by authors from the U.S.-Mexico border region: "Hotel Frontera" ("Border Hotel"), by Gabriel Trujillo Muñoz, "Canícula," by Norma Elia Cantú, and "The Magic of Blood," by Dagoberto Gilb. These narratives provide ethnographic information about the reception of nationally distributed mass media in the border region; at the same time they produce a contestatory discourse that challenges the manner in which the border and its populations have been portrayed and employed in the U.S. and Mexican film industries. The study of film culture must take into consideration patterns of consumption as well as production, and literature about mass media is one arena through which it is possible to focus on both of these processes simultaneously. Fronteriza/o writing about cinema reveals a desire to inhabit popular cinematic genres such as film noir and the western while at the same time retaining a critical stance towards them. This ambivalence is understood as a localist response to the marginalization of fronteriza/o cultural production in a bi-national context, rather than as general suspicion toward visual mass media on the part of "traditional" literary intellectuals.
Keywords: border literature; mass media; Mexico; U.S.; Hollywood; fronterizo/a; bi-national; cinema; identity; culture; visual mass media; tradition; literary intellectualism